1981
DOI: 10.1037/0022-0167.28.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Increase in assertiveness and actualization as a function of didactic training.

Abstract: This study attempted to determine whether didactic training could increase level of assertiveness and actualization. Sixty-five low assertive undergraduate students were randomly assigned to one of five groups. All groups except a no-treatment control group were exposed to three 20-minute video tapes during the course of 1 week. Group 1 was exposed to the didactic principles of Rogerian theory. Group 2 was given the didactic principles of assertiveness theory. All subjects were given a test battery administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…In conclusipn, the assertion literature has seemingly reached an important crossroads wherein existing theoretical formulations are now recognized as incomplete and untested (Galassi & Galassi, 1978). At the same time, investigations of organismic or individual variables such as actualization (Goddard, 1981), state anxiety (Pentz, 1981), and locus of control (Schwartz & Higgins, 1979) are in the ascendant. These developments, in conjunction with the findings of this study, may reintroduce for the counseling practitioner the importance of understanding the underlying motivations and character styles that distinguish even "clinically normal" individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusipn, the assertion literature has seemingly reached an important crossroads wherein existing theoretical formulations are now recognized as incomplete and untested (Galassi & Galassi, 1978). At the same time, investigations of organismic or individual variables such as actualization (Goddard, 1981), state anxiety (Pentz, 1981), and locus of control (Schwartz & Higgins, 1979) are in the ascendant. These developments, in conjunction with the findings of this study, may reintroduce for the counseling practitioner the importance of understanding the underlying motivations and character styles that distinguish even "clinically normal" individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies involving didactic intervention suggest that the effects are long term. Goddard (1981), working with a tertiary student population, actually observed further increases in scale scores over an extended period.…”
Section: Discussionmentioning
confidence: 99%
“…inspirational motivation, hope inspiration). Goddard (1981) viewed hope as inspiration and Cutcliffe (2006) investigated the concept of hope inspiration. Chamorro‐Premuzic (2006) suggested that although creativity has a long history in psychology, it has recently been conceptualized as inspiration.…”
mentioning
confidence: 99%